ETIKA KOMUNIKASI DIGITAL SEBAGAI CERMINAN PENDIDIKAN KARAKTER DALAM KOMENTAR WARGANET PADA AKUN INSTAGRAM @NARASINEWSROOM - Dimas Maulana; Karim Suryadi; Asep Mahfudz (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the practices of digital communication ethics as a reflection of character education in netizen comments regarding freedom of speech on the Instagram account @narasinewsroom. This research employs a qualitative approach using thematic content analysis on comments found in the account's posts. The analytical framework is based on Habermas' communicative action theory and the dimensions of digital communication ethics. The results indicate that digital communication ethics practices in the @narasinewsroom comment section are still uneven; although freedom of speech is actively practiced, the dimensions of digital empathy, responsibility, and civility in communication still require greater attention. Character education values have not been fully integrated into netizens' daily digital behaviors, as evidenced by a substantial number of aggressive or non-objective responses. Strengthening digital literacy based on ethical and civic values is the main recommendation to promote a healthier and more responsible digital communication culture.